Efficient interfacial charge transfer of 2D/2D CoP/CdS heterojunction for extremely boosted photocatalytic H2 evolution performance. (22nd September 2022) - Fu, Manjun; Fan, Guozhi; Ding, Deng; Liu, Yanyu; Yan, Juntao; Wang, Chunlei; Song, Guangsen; Chai, Bo
Abstract: Constructing 2D/2D heterojunction photocatalysts has attracted great attentions due to their inherent advantages such as larger interfacial contact areas, short transfer distance of charges and abundant reaction active sites. Herein, 2D/2D CoP/CdS heterojunctions were successfully fabricated and employed in photocatalytic H2 evolution using lactic acid as sacrificial reagents. The multiple characteristic techniques were adopted to investigate the crystalline phases, morphologies, optical properties and textual structures of heterojunctions. It was found that integrating 2D CoP nanosheets as cocatalysts with 2D CdS nanosheets by Co–S chemical bonds would significantly boost the photocatalytic H2 evolution performances, and the 7 wt% 2D/2D CoP/CdS heterojunction possessed the maximal H2 evolution rate of 92.54 mmol g −1 h −1, approximately 31 times higher than that of bare 2D CdS nanosheets. Photoelectrochemical, steady photoluminescence (PL) and time-resolved photoluminescence (TRPL) measurements indicated that there existed an effective charge separation and migration over 2D/2D CoP/CdS heterojunction, which then markedly lengthened the photoinduced electrons average lifetimes, retarded the recombination of charge carriers, and caused the dramatically boosted photocatalytic H2 evolution activity. Moreover, the density functional theory (DFT) calculation further corroborated that the efficient charge transfer occurred at the interfaces of CoP/CdS heterojunction. This present research puts forward a promising strategy to engineer the 2D/2D heterojunction photocatalysts endowed with an appealing photocatalytic H2 evolution performance. Graphical abstract: 2D/2D CoP/CdS heterojunctions were successfully constructed and employed as the highly efficient photocatalysts for H2 evolution. Image 1 Highlights: 2D/2D CoP/CdS heterojunctions were fabricated by a post-annealing procedure. The multiple characterization techniques were applied to confirm the formation of 2D/2D CoP/CdS heterojunctions. 2D/2D CoP/CdS heterojunctions exhibited the extremely boosted photocatalytic H2 evolution performance. The mechanism for remarkably boosted photocatalytic H2 evolution activity was tentatively proposed.